2010
DOI: 10.1002/mc.20677
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression of normal human epidermal keratinocytes modulated by trivalent arsenicals

Abstract: Chronic exposure to inorganic arsenic (iAs) is associated with the development of benign and malignant human skin lesions including nonmelanoma skin cancers. The precise arsenical form(s) responsible for this carcinogenic effect are unknown, although trivalent inorganic arsenic (iAs(III)) and two of its toxic metabolites, monomethylarsonous acid (MMA(III)) and methylarsinous acid (DMA(III)), are attractive candidates. In an effort to better understand and compare their toxic effects in the skin, we compared th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 85 publications
(114 reference statements)
1
20
0
Order By: Relevance
“…Cells were treated with vehicle control or arsenic as described previously [8]. Arsenic concentrations of 4 and 8 μM were used since previous studies in keratinocytes and other cells indicated arsenic treatment in this dose range is relatively non-cytotoxic and induces signaling modulation consistent with arsenic induced skin carcinogenesis including oxidative stress and autophagy or p62 signaling [8,24,26,38]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cells were treated with vehicle control or arsenic as described previously [8]. Arsenic concentrations of 4 and 8 μM were used since previous studies in keratinocytes and other cells indicated arsenic treatment in this dose range is relatively non-cytotoxic and induces signaling modulation consistent with arsenic induced skin carcinogenesis including oxidative stress and autophagy or p62 signaling [8,24,26,38]. …”
Section: Methodsmentioning
confidence: 99%
“…Cells positive for annexin V-fluorescein isothiocyanate (apoptotic cells) were quantified by flow cytometry using a BD Calibur (BD Biosciences, San Jose, CA, USA). Twenty-five-micromolar arsenic was used since similar concentrations have been indicated for arsenic-induced cytotoxicity in previous studies using in vitro models including keratinocytes [26,38,47]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…83 After analyzing trends in cell proliferation, apoptosis, and the expression of genes promoting cellular oxidative defense, apoptosis factors and growth factors, the study's authors concluded that MMA III was the most cytotoxic species (LC 50 = 2.8µM) , followed by DMA III (LC 50 = 5.6µM), and then iAs III (LC 50 = 17µM). In human bladder cancer cells, treatment with DMA III or DMMTA V (dimethylmonothioarsinic acid) drastically reduced GSH and p53 levels compared to control cells, while iAs also decreased p53 it was not as drastic as DMA III and treatment actually increased GSH levels compared to control.…”
mentioning
confidence: 99%
“…Although the in vitro experiments took place in a short period of time, the observed increase of ROS and antioxidant enzymes in arsenical cancers, but not in non-arsenical cancers, supports the notion that ROS has, at least in part, a role in the initiation and progression of arsenic carcinogenesis. A microarray analysis from arsenictreated keratinocytes also demonstrated that many genes involved in antioxidant responses, including glutathionerelated proteins (GCLC, GCLM, and SLC7A11), thioredoxin (TXNRD1), and the NADPH-dependent protein (PGD), were upregulated (Bailey et al, 2010). Recent studies also showed that selective knockdown of antioxidant enzymes significantly sensitized keratinocytes to arsenic cytotoxicity (Zhao et al, 2012).…”
Section: Discussionmentioning
confidence: 95%